Exploring the pteridophyte flora of the Eastern Afromontane biodiversity hotspot. Issue 6 (November 2016) - Liu, Hong‐Mei; Zhang, Shou‐Zhou; Wan, Tao; Kamau, Peris W.; Wang, Zheng‐Wei; Grall, Aurelie; Hemp, Andreas; Schneider, Harald
Abstract: In this review, we explore our current understanding of the fern and lycophyte diversity occurring in the Eastern Afromontane Biodiversity Hotspot (EABH). The review explores the species diversity of this region in the context of the Afromadagascan pteridophyte diversity based on an exhaustive species list assembled in the synopsis of Afromadagascan pteridophytes published by Roux in 2009. The list was updated by incorporating recent progress in our understanding of the taxonomy and phylogeny of these plants. Evidence for a distinct pteridophyte flora occurring in the East African mountain region was discovered using ordination and clustering analyses. This EABH floras shares links to other Afromadagascan pteridophyte floras such as the one in the tropical lowland forests of central and western Africa. These floras share the dominance of species that preferably occur in humid climates whereas other African pteridophyte floras tend to contain a higher proportion of xeric adapted ferns. The phylogenetic composition of the EABH pteridophyte flora was assessed by comparing global versus local proportion of orders, families, and genera. This analysis revealed distinct patterns that are partly caused by the radiation of Blotiella and Triplophyllum besides selective colonization of species pre‐adapted to Afromadagascan climates. In situ speciation in the East African tropical mountains may have contributed to the global diversity of widespread genera such as Asplenium and Pteris . In summary, this is the first comprehensive attempt to assess the pteridophyte diversity of the East African mountains providing the framework for future studies on their conservation, ecology, and evolution.